Therapeutic Potential of Induced Neural Stem Cells for Spinal Cord Injury - Hong, Jin Young (J Biol Chem, 2014)
The spinal cord does not spontaneously regenerate, and treatment that ensures functional recovery after spinal cord injury (SCI) is still not available. Recently, fibroblasts have been directly converted into induced neural stem cells (iNSCs) by the forced expression defined transcription factors. Although directly converted iNSCs have been considered to be a cell source for clinical applications, their therapeutic potential has not yet been investigated. Here we show that iNSCs directly converted from mouse fibroblasts enhance the functional recovery of SCI animals. Engrafted iNSCs could differentiate into all neuronal lineages, including different subtypes of mature neurons. Furthermore, iNSC-derived neurons could form synapses with host neurons, thus enhancing the locomotor function recovery. A time course analysis of iNSC-treated SCI animals revealed that engrafted iNSCs effectively reduced the inflammatory response and apoptosis in the injured area. iNSC transplantation also promoted the active regeneration of the endogenous recipient environment in the absence of tumor formation. Therefore, our data suggest that directly converted iNSCs hold therapeutic potential for treatment of SCI and may thus represent a promising cell source for transplantation therapy in patients with SCI.